Design of Recapitulation System Pending Inpatient Claims to Enhance BPJS Verification Efficiency Using Extreme Programming - Belinda Nuryania Prameswari; Falaah Abdussalaam; Yuyun Yunengsih (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
This study designs and develops an information system with a centralized database for recapitulating pending inpatient claims at Hospital X Bandung. The system assists casemix officers in optimizing report accuracy, analyzing frequent ineligible claim types, and minimizing recurrent case probability. Hospital X currently employs a conventional Excel-based process lacking centralized analytics for case classification and periodic data management. The research methodology employs Extreme Programming (XP), selected for its rapid iteration cycles, flexibility, and continual improvement capabilities. Data collection combines direct observations, structured interviews with four medical record installation officers, and systematic literature review. The XP approach enables iterative development with continuous user feedback, ensuring the system meets operational requirements. Implementation results demonstrate measurable improvements: processing time decreased by 35%, pending claim rates reduced by 40%, and classification accuracy increased by 75%. The system architecture comprises four modules: data entry, claim case classification, report generation, and dashboard visualization. Each module underwent rigorous testing through Black Box Testing methodology, validating functionality and user experience. Current system constraints include absence of INA-CBGs system integration, advanced data encryption protocols, and cross-network usage capabilities. The standalone desktop architecture limits simultaneous multi-user access. Despite these constraints, the system successfully simplifies recapitulation workflows and establishes a foundation for future development, particularly web-based architecture and predictive analytics integration